CONFINEMENT OF MICRONUCLEUS ON DAWKINSIA TAMBRAPARNIEI BY THE PARADOXICAL EFFECT OF THE ARSENIC DERIVATIVES - Velu, Vijay; Uthandakalaipandian, Ramesh (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: In the current study, in vivo genotoxic effects of arsenic derivatives such as arsenic trioxide (As2O3) and sodium arsenite (NaAsO2) on peripheral blood erythrocytes of Dawkinsia tambraparniei were investigated using the micronucleus (MN) test. Methods: MN staining was done using acridine orange pre-coated slides. Fluorescent microscope was used for scoring. Results: In NaAsO2 exposed, the erythrocytes highest value was recorded at 42 days which is twofold higher than exposure at 7 days when compared to As2O3. Highest percentage was recorded about 13.9 in NaAsO2, and in case of As2O3, it was recorded as 0.2% less. It was clearly confirmed that either form of arsenic is toxic to organism. Conclusion: Anthropogenic activities have also brought in substantial amounts of them into the environment by mobilization from their natural insoluble deposits or environmental sins. Hence, arsenic pollution should have measured, and arsenic removal process should have carried out.